2020
DOI: 10.3389/fimmu.2020.565458
|View full text |Cite
|
Sign up to set email alerts
|

Activated Human Memory B Lymphocytes Use CR4 (CD11c/CD18) for Adhesion, Migration, and Proliferation

Abstract: Complement receptors CR3 (CD11b/CD18) and CR4 (CD11c/CD18) of myeloid cells are known for long to participate in actin linked functions like phagocytosis, adhesion, and migration. The expression and role of these two β 2 -integrins however, in human B lymphocytes have only scarcely been studied so far, although it has been shown recently that CD11c + B cells are mainly memory cells. In our systematic study we investigated B cells isolated from tonsils and periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…In the case of healthy donors it has been found, that these receptors are scarcely expressed on nonactivated B lymphocytes [4,5], but after activation by different stimuli they appear on certain B cell populations [5][6][7][8][9][10]. We found lately that activated human memory B lymphocytes use CR4 for adhesion, migration, and proliferation [11].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In the case of healthy donors it has been found, that these receptors are scarcely expressed on nonactivated B lymphocytes [4,5], but after activation by different stimuli they appear on certain B cell populations [5][6][7][8][9][10]. We found lately that activated human memory B lymphocytes use CR4 for adhesion, migration, and proliferation [11].…”
Section: Introductionmentioning
confidence: 76%
“…Recently, our group demonstrated that both CR3 and CR4 are involved in the spreading of CpG-activated CLL B cells on fibrinogen [4]. Moreover, since activated B cells of healthy donors use CR4 for adhesion, migration, and proliferation [11], we suggest that CR4 may have a similar role in CLL B cells too, as malignant cells represent the activated state of their normal counterpart.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In humans, CD11b and CD11c are simultaneously present on a wide variety of leukocytes, but they are expressed on phagocytes in the greatest number (Erdei et al 2017;Nagy-Baló et al 2020). Moreover, CD11c is a generally accepted myeloid marker in humans.…”
Section: The Integrinsmentioning
confidence: 99%
“…The complement receptors CR3 and CR4 are expressed on monocytes, macrophages, dendritic cells, neutrophils and natural killer cells, and recently they have been detected on certain B lymphocyte populations in human (Erdei et al 2017;Nagy-Baló et al 2020).…”
Section: Expression Of Cr3 and Cr4 On Myeloid Cellsmentioning
confidence: 99%